Benthic Prey in a Bowhead Whale from the Northern Bering Sea - Hazard, Katherine W.; Lowry, Lloyd F. (ARCTIC, 1984)
Stomach contents were examined from a bowhead whale, Balaena mysticetus, killed at Gambell, Alaska, on 1 May 1982. It contained an estimated 20-40 litres of recently ingested prey, principally gammarid amphipods (91.7% of the volume of a 157-ml subsample) and cumaceans (7%). All identified prey were primarily epibenthic forms. The stomach of this whale was significant in several respects: (1) it contained the largest amount of food recorded in any whale taken and examined in spring; (2) it provided the first direct evidence of bowheads feeding in the Bering Sea; and (3) the contents indicated that benthic prey are sometimes intentionally fed upon.Key words: Balaena mysticetus, benthic prey, Bering Sea, bowhead whale, feeding, gammarid amphipods Mots clés: Balaena mysticetus, proie benthique, mer de Béring, baleine boréale, alimentation, amphipodes gammaridés